Rafiq Syndrome: Old Variant in MAN1B1 Gene and Some New Phenotypic Features - Özgün, Nezir; Merve Saka Güvenç, Merve (Iranian Journal of Child Neurology, 2025)
Rafiq syndrome is a congenital disorder of glycosylation type II that develops due to mutations in the Mannosidase Alpha Class 1B Member 1 (MAN1B1) gene encoding α 1,2-mannosidase. In the literature, 45 patients have been reported to date. This study presents a patient with some phenotypic traits that differ from previously reported patients with Rafiq syndrome.Since the patient was not diagnosed despite detailed examinations, whole exome sequencing was performed. The patientss’ homozygous c.1000 C>T (p.Arg334Cys) pathogenic variant was detected in the MAN1B1 gene (NM_016219.5), which was consistent with Rafiq syndrome. Our patient’s clinical findings were mainly similar to those of previously reported patients. However, our patient had feeding difficulty that started to improve after the fifth month and persistent hyperekplexia . Feeding difficulty and hyperekplexia concomitant to MAN1B1 gene mutation are reported for the first time. More extensive case series are needed to understand whether these findings are part of the syndrome or incidental comorbid conditions